Haemophilia gene therapy—Update on new country initiatives. (6th May 2022) - Reiss, Ulrike M.; Mahlangu, Johnny; Ohmori, Tsukasa; Ozelo, Margareth C.; Srivastava, Alok; Zhang, Lei
Abstract: Introduction: Gene therapy is emerging as a potential cure for haemophilia. Gene therapy is a one‐time treatment that can elevate factor levels for many years and minimize or eliminate the need for clotting factor concentrate (CFC) replacement therapy. However, there is a paucity of reports on gene therapy efforts in countries outside of North America or Europe, especially in low‐and‐middle‐income countries (LMIC). All indications are that gene therapy will be one of standard care treatments for haemophilia in the future. Still, it may not be accessible to many countries due to various barriers and challenges. At the same time, each country may formulate solutions that may be used globally. Aim: To summarize the approaches taken to establish haemophilia gene therapy in Japan, China, India, South Africa, and Brazil, and to describe the US‐initiated multi‐LMIC haemophilia gene therapy development program to include Peru, Vietnam, Thailand, Nepal, and Sri Lanka. Methods: A review of related published information or as accessible by each country's author. Results: Different starting conditions, differing input and level of support from the multitude of stakeholders, and strong leadership have led to various approaches for facilitating research and developing needed infrastructure and regulatory and financing models. Gene therapy programs are at various stages of development and include both adeno‐associated viral and lentiviral vectors. Conclusion: Global partnerships and collaboration, exchange of knowledge and experience, and alignment of processes across borders will promote further progress towards global access to gene therapy for haemophilia. Abstract :